Numerical analyses of laminar flames propagating in droplet mists using detailed and tabulated chemistry. Issue 5 (3rd September 2018) - Sacomano Filho, Fernando Luiz; Speelman, Nico; van Oijen, Jeroen Adrianus; de Goey, Laurentius Philippus Hendrika; Sadiki, Amsini; Janicka, Johannes
Abstract : Numerical analyses of laminar flames propagating in mono-dispersed quiescent droplet mists are addressed. Attention has been given to the evolution of combustion reactions interacting with different mists and the assessment of chemistry simplifications. In the first part, investigations are exclusively performed in a detailed description of the chemistry. Focus is concentrated on simplifications typically assumed in simulations of turbulent spray combustion. Namely, evaporative cooling and differential diffusion. These phenomena are systematically studied together with the characteristics of the observed flammability limits. In the second part, simulations conducted with the flamelet generated manifold (FGM) method are compared with detailed chemistry results. Flame propagation speed and profiles of selected quantities are used. Results demonstrate to what extent common simplifications applied to turbulent spray combustion, as well as FGM tables constructed with single-phase flamelets, are suitable for representing spray flame characteristics.